Developing bilingual expressions pocketbook for secondary students at Assalafiyah Language Center (ALC) - Azmi, Ulul; Aminah, Aminah; Kholis, Adhan (Universitas Islam Malang, 2024)
The objective of this research was to develop bilingual expressions pocketbook. This research used the type of research and development (RnD) that applied the ADDIE model, which employed five steps, including analysis, design, development, implementation, and evaluation. The product of the research was bilingual expressions pocketbook. The contents of the pocketbook consist of a cover, vocabularies of each topic, and the expressions of each topic. This research was conducted in ALC’s Secondary Students at Assalafiyah, which contained 27 students. In collecting data, the researchers employed some techniques like interviews, questionnaires, tests, and documentation. The result of this research showed that the validation result from the material expert was an average of 3.5. It was categorized as very good. The validation result from the media expert was average, which is 3.6. It was categorized as very good. Therefore, it can be concluded that developing bilingual expressions pocketbook is appropriate to be implemented at ALC. Also, the development of a bilingual expressions pocketbook for Secondary Students at Assalafiyah Language Center (ALC) holds significant promise for enhancing language learning and communication skills. The design phase focuses on creating clear and measurable learning objectives, selecting appropriate instructional strategies, and devising assessment methods that cater to the unique bilingual context. The pocketbook provided students with a handy reference for learning and practicing common bilingual expressions. Also, it can increase students’ motivation and engagement in learning vocabularies.